TLR2−/− Mice Display Increased Clearance of Dermatophyte Trichophyton mentagrophytes in the Setting of Hyperglycemia - Almeida, Débora de Fátima; Fraga-Silva, Thais F. de Campos; Santos, Amanda R.; Finato, Angela C.; Marchetti, Camila M.; Golim, Marjorie de Assis; Lara, Vanessa S.; Arruda, Maria S. P.; Venturini, James (Frontiers in Cellular and Infection Microbiology, 2017)
Dermatophytosis is one of the most common human infections affecting both immunocompetent individuals and immunocompromised patients, in whom the disease is more aggressive and can reach deep tissues. Over the last decades, cases of deep dermatophytosis have increased and the dermatophyte-host interplay remains poorly investigated. Pattern recognition molecules, such as Toll-like receptors (TLR), play a crucial role against infectious diseases. However, there has been very little research reported on dermatophytosis. In the present study, we investigated the role of TLR2 during the development of experimental deep dermatophytosis in normal mice and mice with alloxan-induced diabetes mellitus, an experimental model of diabetes that exhibits a delay in the clearance of the dermatophyte, Trichophyton mentagrophytes (Tm). Our results demonstrated that inoculation of Tm into the footpads of normal mice increases the expression of TLR2 in CD115+Ly6Chigh blood monocytes and, in hypoinsulinemic-hyperglycemic (HH) mice infected with Tm, the increased expression of TLR2 was exacerbated. To understand the role of TLR2 during the development of murine experimental deep dermatophytosis, we employed TLR2 knockout mice. Tm-infected TLR2-/- and TLR2+/+ wild-type mice exhibited similar control of deep dermatophytic infection and macrophage activity; however, TLR2-/- mice showed a noteworthy increase in production of IFN-γ, IL-10, and IL-17, and an increased percentage of splenic CD25+Foxp3+ Treg cells. Interestingly, TLR2-/- HH-Tm mice exhibited a lower fungal load and demonstrated superior organization of tissue inflammatory responses, with high levels of production of hydrogen peroxide by macrophages, alongside low TNF-α and IL-10; high production of IL-10 by spleen cells; and increased expansion of Tregs. In conclusion, we demonstrate that TLR2 diminishes the development of adaptive immune responses during experimental deep dermatophytosis and, in a diabetic scenario, acts to intensify a non-protective inflammatory response.